Genetic transparency? : ethical and social implications of next generation human genomics and genetic medicine - Dreyer, Malte, 1979-; Erdmann, Jeanette, 1965-; Rehmann-Sutter, Christoph, 1959- (Life Sciences, Ethics and Democracy, 2016)
Genetic Transparency? tackles the question of who has, or should have access to personal genomic information. Genomic science is revolutionary in how it changes the way we live, individually and together, and how it changes the shape of society. If this is so, then - the authors of this volume claim - the rules that regulate genetic transparency should be debated carefully, openly and critically. It is important to see that the social and cultural meanings of DNA and genetic sequences are much richer than can be accounted for by purely biomedical knowledge. In this book, an international group of leading genomics experts and scholars from the humanities and social sciences discuss how the new accessibility of genomic information affects interpersonal relationships, our self-understandings, ethics, law, and healthcare systems. Contributors are: Kirsten Brukamp, Gabrielle Christenhusz, Lorraine Cowley, Malte Dreyer, Jeanette Erdmann, Andrei Famenka, Teresa Finlay, Caroline Fündling, Shannon Gibson, Cathy Herbrand, Angeliki Kerasidou, Lene Koch, Fruzsina Molnár-Gábor, Tim Ohnhäuser, Christoph Rehmann-Sutter, Benedikt Reiz, Vasilja Rolfes, Sara Tocchetti